Indigenous Peoples’ Natural Resource Rights: Why Environmental Law Protection Fails in Indonesia? - Vinata, Ria; Sadiyah, Nur Khalimatus; Kartoningrat, Raden Besse; Cassandro, Izan Mateo; Mubaarak, Zulfikar Ahmad Husni (UIR Press, 2026)
Indonesia possesses abundant natural resources and is home to hundreds of indigenous communities whose customary territories have long been managed through traditional ecological knowledge that supports environmental sustainability. Despite constitutional and statutory recognition of indigenous peoples' natural resource rights, persistent conflicts over land, forests, and resource exploitation demonstrate significant weaknesses in their legal protection. This study examines the protection of indigenous peoples' natural resource rights from the perspective of environmental law, and the legal and institutional obstacles that hinder effective implementation. The research employs a normative legal method using statutory and conceptual approaches by analyzing the 1945 Constitution, Law No. 5 of 1960, Law No. 32 of 2009, Constitutional Court Decision No. 35/PUU-X/2012, ILO Convention No. 169, and the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) 2007. The findings reveal that Indonesia has established a relatively comprehensive legal framework recognizing indigenous peoples’ rights, however, this recognition remains largely declaratory because it is not supported by coherent implementing legislation or effective institutional mechanisms. Consequently, indigenous communities continue to experience tenure insecurity, overlapping land claims, exclusion from decision-making, and unequal access to justice. The study demonstrates that the principal failure lies not in the absence of legal recognition but in fragmented governance and weak enforcement. It contributes by proposing integrated legal and institutional reforms that align environmental protection with the effective realization of indigenous peoples’ natural resource rights.